Creativity as an experience and as a complexity: visual-narrative research of the artworks of Tsipy Amos Goldstein - Marnin-Distelfeld, Shahar (Creativity Studies, 2023)
This article focuses on the work Seven Private Skies (initiated in 2009) by the Israeli artist, Tsipy Amos Goldstein. This is a series of large panels on which the artist has been painting and embroidering for fourteen years as her main occupation. The aim of the study was to establish the meanings inherent in the work, which is a kind of multi-layered cryptograph, while characterizing it in terms of creativity. The research method combined visual-interpretive analysis with both a narrative-feminist paradigm and with theories from the field of creativity studies. The findings showed that the series “tells” through artistic means the artist’s personal story in a way that matches two definitions: creativity as an experience and creativity as a complexity. The article will discuss the characteristics of the artist and artwork as an experience and then will present the paradoxes distinguishing the work as complex: 1. Order versus chaos; 2. Love and home in the face of disintegration; 3. Cuts versus connections and male versus female; 4. Understandable communication in the face of conflicting messages; 5. Star of David versus the Jewish yellow badge.